1976
DOI: 10.2307/2060529
|View full text |Cite
|
Sign up to set email alerts
|

Length of residence, social ties, and economic opportunities

Abstract: This study examines length of residence for movers--that subsection of the population which accounts for the high mobility rates in the United States. The propensity for repeated migration is studied in relation to economic opportunities and previous familial and personal contacts. The results indicate no influence of economic opportunities on duration of residence. This finding is consistent with recent research that indicates economic conditions are not a general stimulus for out-migration, although they are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Since Bogue's early review, length of residence and home ownership have been identified as being important and consistently associated with migration (Haan 2007;White and Lindstrom 2006). Studies focusing on these two individual level characteristics maintain that they index socioeconomic ties individuals have established with places (DaVanzo and Morrison 1981; Green and Hendershott 2001;Speare 1970;Toney 1976). Early on, Speare (1970) compared home owners and renters and found renters to be four to five times more likely to move than home owners.…”
Section: Individual Level Characteristics and Migrationmentioning
confidence: 99%
“…Since Bogue's early review, length of residence and home ownership have been identified as being important and consistently associated with migration (Haan 2007;White and Lindstrom 2006). Studies focusing on these two individual level characteristics maintain that they index socioeconomic ties individuals have established with places (DaVanzo and Morrison 1981; Green and Hendershott 2001;Speare 1970;Toney 1976). Early on, Speare (1970) compared home owners and renters and found renters to be four to five times more likely to move than home owners.…”
Section: Individual Level Characteristics and Migrationmentioning
confidence: 99%
“…An exception in the migration literature is the study by Toney [42], which investigates the deterrence effects of social ties on households' migration decision, based on a small scale longitudinal dataset. His sample consists of Rhode Island individuals who had lived in another state prior to moving to Rhode Island, and his indicators of social ties pertain to the states of birth of a respondent and her spouse, and those of their parents, as well as the current states of residence of their parents.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that social ties (i.e., the birthplace of the subject, the subject's spouse and parents being in Rhode Island, or the current state of residence of the subject's parents being in Rhode Island) have a positive impact on the length of stay in Rhode Island. However, in addition to the lack of representativeness of Toney's [42] sample, the social ties' measures used in the study are rather crude and the effects of these variables on migration may instead stem from one's psychological attachment to Rhode Island.…”
Section: Introductionmentioning
confidence: 99%
“…This is the idea that an individual's time of residence in a locale lowers the probability of emigration, thus contributing to a reduction in population turnover at the level of place (Herting, Grusky, and Van Rompaey, ; Land, ). While research on the axiom of cumulative inertia conceptualizes the temporal dynamics of migration as an individual‐level process (Land, ; McGinnis and Pilger, ; McGinnis, ; Morrison, ; Myers, McGinnis, and Masnick, ; Roseman, ; Toney, ), there are important theoretical and policy reasons for understanding these dynamics as a property of place.…”
Section: Theoretical and Policy Frameworkmentioning
confidence: 99%